2019
DOI: 10.3390/w11061265
|View full text |Cite
|
Sign up to set email alerts
|

Coastal and Marine Quality and Tourists’ Stated Intention to Return to Barbados

Abstract: Seawater quality is critical for island and coastal communities dependent on coastal tourism. Improper management of coastal development and inland watersheds can decrease seawater quality and adversely impact marine life, human health, and economic growth. Agricultural runoff and improper sewage management compromise nearshore water quality in many coastal regions and can impact visitation decisions of tourists who are drawn to these destinations. The purpose of this paper is to understand how tourists’ decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Hotels may become point source if wastewater is discharged to the lagoon without advance treatment systems. This is a matter of great concern, not least because there is growing evidence (Halkos and Matsiori, 2018;Schuhmann et al, 2019) that water quality is the single most important factor contributing to the decision of tourists to revisit a particular seaside location.…”
Section: Nutrient Dynamics the Negombo Lagoonmentioning
confidence: 99%
“…Hotels may become point source if wastewater is discharged to the lagoon without advance treatment systems. This is a matter of great concern, not least because there is growing evidence (Halkos and Matsiori, 2018;Schuhmann et al, 2019) that water quality is the single most important factor contributing to the decision of tourists to revisit a particular seaside location.…”
Section: Nutrient Dynamics the Negombo Lagoonmentioning
confidence: 99%
“…Additionally, Schuhmann et al (2019) affirm that return decisions are sensitive to changes in all aspects of coastal and marine quality. Lam‐González, León, and De León (2020) found that affective feelings towards the nautical destination were an important antecedent of satisfaction in nautical tourists.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The selection of these environmental factors is carried out based on the impact on that environmental condition. The most important environmental factors for dive tourism are visibility and life-coral reefs (HCL) [17]. Water visibility is known to be most crucial factors because it represents the sunlight penetration into the water.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal water visibility for coral life is 100% [6]. The high antrophogenic activities in the land might transfer a high number of both suspended and particulate materials to the Tanung Benoa waters, causing low water visibility [5,17]. These materials inhibit the penetration of sunlight in the water and disturb the growth of coral reefs [3].…”
Section: Discussionmentioning
confidence: 99%